Identification of oxidosqualene cyclases from the medicinal legume tree Bauhinia forficata: a step toward discovering preponderant α‐amyrin‐producing activity. Issue 1 (4th August 2019) - Srisawat, Pisanee; Fukushima, Ery Odette; Yasumoto, Shuhei; Robertlee, Jekson; Suzuki, Hideyuki; Seki, Hikaru; Muranaka, Toshiya
Summary: Triterpenoids are widely distributed among plants of the legume family. However, most studies have focused on triterpenoids and their biosynthetic enzymes in model legumes. We evaluated the triterpenoid aglycones profile of the medicinal legume tree Bauhinia forficata by gas chromatography–mass spectrometry. Through transcriptome analyses, homology‐based cloning, and heterologous expression, we discovered four oxidosqualene cyclases (OSCs) which are responsible for the diversity of triterpenols in B. forficata . We also investigated the effects of the unique motif TLCYCR on α‐amyrin synthase activity. B .  forficata highly accumulated α‐amyrin. We discovered an OSC with a preponderant α‐amyrin‐producing activity, which accounted for at least 95% of the total triterpenols. We also discovered three other functional OSCs (BfOSC1, BfOSC2, and BfOSC4) that produce β‐amyrin, germanicol, and cycloartenol. Furthermore, by replacing the unique motif TLCYCR from BfOSC3 with the MWCYCR motif, we altered the function of BfOSC3 such that it no longer produced α‐amyrin. Our results provide new insights into OSC cyclization, which is responsible for the diversity of triterpenoid metabolites in B .  forficata, a non‐model legume plant.